Solar Thermoelectric Generator (STEG) for Lighting System - Husainy, Muhamad Fakhrul Amri; Mohamad Rosli, Muhammad Afiq; Norizan , Muhd Zul Syafiq; Saifullah Arifin , Nur Hidayah; Mahathir, Nur Qistina Eiman; Saleh, Umar Abubakar; Jumaat , Siti Amely (Evolution in Electrical and Electronic Engineering, 2021)
The Covid-19 pandemic has dramatically affected the B40 household in Malaysia. One effective method to lessen the burden of this is to conduct an optimal electrical energy consumption to minimize everyday expenses such as a thermoelectric generator. However, around 2.8 million B40 communities were estimated to have lost their jobs as a result of the Covid-19 outbreak in March 2020, resulting in financial difficulties. Therefore, this project discussed developing a prototype solar thermoelectric generator (STEG) for a lighting system using renewable energy. The significant parts of this project consist of the Peltier plate module, LED, wire, heat sink, fan, and battery. The Peltier plate module which is known as thermoelectric plate absorbs the sunlight, which will later cause a temperature differential that produces electricity through the Seebeck effect. The efficiency of a STEG is thus determined by both the efficiency with which sunlight is transformed to heat and the device's thermoelectric efficiency. Its efficiency depends on the temperature difference between the sides of the thermoelectric generator plates.